PAJAK PENGHASILAN ATAS PENGHASILAN DARI PENGALIHAN HAK ATAS TANAH DAN/ATAU BANGUNAN, DAN PERJANJIAN PENGIKATAN JUAL BELI ATAS TANAH DAN/ATAU BANGUNAN BESERTA PERUBAHANNYA - Desy Arsita Kusumadewi, 12.05.52.0002; Kartika, Andi (Students' Journal of Accounting and Banking, 2016)
This research analyze the influence of good corporate governance againt tax avoidance. Good corporate governance are measure by institusional ownership, proportion of  commisioner independent board, the audit quality, and the audit commitee. This research sample is manufactured industry company registred on Indonesia Stock Exchange during the year 2013-2015 by using of method purposive sampling. The are 114 companies in accordance with the appropriate criteria. This research used multiple regression analysis. The results of this research indicates that institusional ownership, proportion of commisioner independent board, the audit commitee significantly affect the tax avoidance. While the audit quality does not significantly affect the tax avoidance. While the audit quality does not significantly affect the tax avoidance. The limitation of the study used the manufactured companies that whole shares were listed in the indonesia stock exchange, so the reult can be deduced for each industry sector.Keywords: Good Corporate Governance, Tax Avoidance, Institusional Ownership, Proportion of Commisioner Independent Board, The Audit Quality and The Audit Commitee